Cisplatin encapsulated nanoparticles from polymer blends for anti-cancer drug delivery. (8th March 2022) - Joshy, K. S.; Augustine, Robin; Hasan, Anwarul; Ali Zahid, Alap; Alex, Susan M.; Dalvi, Yogesh B.; Mraiche, Fatima; Thomas, Sabu; Kalarikkal, Nandakumar; Chi, Hong
Abstract : Synthesis of cubic nanostructure for cisplatin encapsulation. Abstract : Developing novel nanocarriers for anticancer drug delivery has become a 'promising niche'. The toxicity of the carrier and its efficacy in treatment modalities have become cardinal points as they can impede the progress of the therapy. In this study, a drug delivery system composed of a blend of polymers coated with a lipid, which is able to release cisplatin efficiently, was contrived. Here, cisplatin was encapsulated inside thermo-responsive dextran/gelatine blend nanocarriers coated with a lipid-PEG shell. The cisplatin encapsulated nanoparticles had a cube-like structure with a mean diameter of 210.25 ± 31.58 nm. The developed drug delivery system has showed a drug loading capacity of more than 90% and exhibited pH-responsive release of cisplatin. Moreover, the desirable features of the nanoparticles include biodegradability, biocompatibility, and blood compatibility. The potency of the drug delivery system was tested against breast cancer cells (MDA-MB 231), which provided excellent results establishing the vigour of cisplatin-loaded nanoparticles in human breast cancer interventions. Furthermore, imperceptible systemic toxicity and side effects and its anti-tumor effects make cisplatin-loaded nanoparticles predominate as an eminent tool in cancer therapy.